Silicon nanowire interface circuit for DNA detection - Usman, Kamilu Iman; Hamidon, Mohd Nizar; Abd Rahman, Siti Fatimah; Sim, Guan Ling (Universiti Putra Malaysia Press, 2017)
Detection and quantification of DNA is critical to many areas of life sciences and health care, from disease diagnosis to drug screening. The transduction of DNA through electrochemical methods have a fast response rate and with a conductometric device like the silicon nanowire which can be fabricated to have a similar diameter of the DNA molecule being targeted, detection is real-time. Critical to this is the interfacing of a current-source and an amplifier capable of achieving a maximum of 10 pico ampere input bias. In this project, we fabricated a silicon nanowire using the top down approach and built a circuit that can mimic the output signal as low as 12 nA and achieved a gain of 1 million to be interfaced with the nanowire for real-time DNA detection.